Characterization, Quantification, and Molecular Identification of Co-Infection of Canine Parvovirus (CPV-2) Variants in Dogs Affected by Gastroenteritis in Ecuador During 2022–2023 - Anthony Loor-Giler; Silvana Santander-Parra; Sara Castillo-Reyes; Martin Campos; Renán Mena-Pérez; Santiago Prado-Chiriboga; Luis Nuñez (Veterinary Sciences)
Canine parvovirus (CPV-2) is a highly contagious virus in canines, and it is mostly spread by touching infected feces. Dogs of all ages can catch it, but puppies are more likely to suffer from it. Severe signs include vomiting, diarrhea with blood, feeling tired, and not drinking enough water. There are three different types of the original CPV-2 that have been found so far, which are CPV-2a, 2b, and 2c. The genome of CPV-2 is about 5.2 kb long and has two open reading frames (ORFs), namely the VP region and the NS region. Based on changes in amino acids at position 426, the VP2 protein distinguishes the gene apart in the VP region. Using a molecular method, this study contemplated the presence of CPV-2 and its variants in dogs that had gastroenteritis, as well as other infections. There were 511 samples tested, and 401 (78.47%) of them were positive for CPV-2. Of these, 144 (25.91%) were positive for the original genotype, 258 (64.34%) for genotype 2a, 343 (85.54%) for genotype 2b, and 167 (41.65%) for genotype 2c. Using the multiplex qPCR for genotyping, CPV-2a and CPV-2b were determined as the most frequent co-infections (16.45%). The three genotypes (2a, 2b, and 2c) were found in the samples examined based on the amino acids at position 426 of the VP2 protein, as demonstrated by the VP2 gene sequencing. Furthermore, it was discovered that in certain samples, a genetic modification at position 297 was connected to the virus’s pathogenicity.